2020
DOI: 10.1101/2020.05.26.116533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortex cis-regulatory switches establish scale colour identity and pattern diversity inHeliconius

Abstract: 22The wing patterns of butterflies are an excellent system with which to study phenotypic evolution. The 23 incredibly diverse patterns are generated from an array of pigmented scales on a largely two-24 dimensional surface, resulting in a visibly tractable system for studying the evolution of pigmentation. 25In Heliconius butterflies, much of this diversity is controlled by a few genes of large effect that regulate 26 pattern switches between races and species across a large mimetic radiation. One of these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 81 publications
2
20
0
Order By: Relevance
“…The Optix-bound dome/wash promoter was not classified as an adaptive hub, indicating that while many loci associated with selection on Optix binding sites form adaptive hubs, strong candidate loci for color pattern-associated divergence are not limited to hub loci. dome has been previously implicated in multiple butterfly wing patterning roles, including yellow mimicry patterns in Heliconius (29,30). Specifically, the study of the presence or absence of a yellow hindwing bar phenotype in H. melpomene found a significant association between single-nucleotide polymorphisms (SNPs) at the dome/wash locus and the yellow bar pattern.…”
Section: Optix-bound Loci Under Selection Differentiate Postman From mentioning
confidence: 99%
“…The Optix-bound dome/wash promoter was not classified as an adaptive hub, indicating that while many loci associated with selection on Optix binding sites form adaptive hubs, strong candidate loci for color pattern-associated divergence are not limited to hub loci. dome has been previously implicated in multiple butterfly wing patterning roles, including yellow mimicry patterns in Heliconius (29,30). Specifically, the study of the presence or absence of a yellow hindwing bar phenotype in H. melpomene found a significant association between single-nucleotide polymorphisms (SNPs) at the dome/wash locus and the yellow bar pattern.…”
Section: Optix-bound Loci Under Selection Differentiate Postman From mentioning
confidence: 99%
“…cortex , a cell cycle regulator, plays a role in melanin synthesis in Biston betularia and Heliconius butterflies (Nadeau et al, 2016; van’t Hof et al, 2016). Loss of cortex affects black pigmentation and increase the extent of the upper lamina of the black scales (Livraghi et al, 2020). In sum, these experiments suggest that ommochromes and melanins such as dopa-melanin, dopamine-melanin, xanthommatin, and dihydroxanthommatin might be directly involved in polymerizing chitin in particular patterns inside a scale cell and in regulating scale morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of the gene appears to be more complex than initially envisioned. Although previous expression studies using in situ hybridization have shown a strong correlation between the position of cortex mRNA in wing disks of fifth instar larvae and distal black pattern elements in the adult wings of H. numata and H. melpomene (Nadeau et al, 2016;Saenko et al, 2019), the color switches induced by cortex knockouts (KOs) do not seem to act in a pattern specific way in H. erato and H. melpomene (Livraghi et al, 2020). Instead, cortex KOs result in ectopic switches from melanic (Type II) and red/brown/orange (Type III) into white/yellow (Type I) scale cells across the whole surface of both wings in H. erato and H. melpomene.…”
Section: From Patterns To Process -A Model Of Wing Pattern Evolutionmentioning
confidence: 96%
“…In H. numata, variation around the region that contains cortex controls all variation in wing patterns and is responsible for differences in yellow, orange, and black pattern elements among sympatric color pattern morphs (Nadeau et al, 2016;Saenko et al, 2019). cortex KO results in the appearance of Type I scales across the wing surface of Heliconius butterflies (see Livraghi et al, 2020). The signaling ligand WntA is on chromosome 10 and variation around the locus is associated with differences in forewing band size, shape and position in H. erato and other Heliconius species.…”
Section: From Patterns To Process -A Model Of Wing Pattern Evolutionmentioning
confidence: 99%
See 1 more Smart Citation